Pembajakan Karya di Bidang Hak Cipta: Telaah Integratif Hukum Islam dan Undang-Undang R.I. Nomor 28 Tahun 2014 tentang Hak Cipta - Syufa'at Syufa'at (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2019)
Copyright is one part of intellectual property that has the widest scope of protected objects. The rapid development of information and communication technology requires rules that support copyright, especially with the rampant piracies. Therefore, copyright must have a legal protection as other rights. This paper is dedicated to outlining the concept of piracy of works in the field of copyright using an integrated review of Islamic law and the Indonesian Law No. 28 of 2014 concerning Copyright. By using a deductive framework and normative approach, this paper formulates one finding that copyright piracy even though there are no clear and standard rules in Islamic law, by using analogy (qiyÄs) method, the copyright rule is in accordance with the law against the perpetrator of theft (saraqah). However, because a pirator of copyrights is not the same as a theft, its rule enters taâ€™zÄ«r domain where all provisions for sanctions are determined by the government. In Indonesia, the actualization of sanctions is regulated in Law No. 28 of 2014, which essentially strives to create justice and guarantee of every individual right that leads to widespread benefit. Islamic law (in this case saraqah rules) becomes the theological basis for Law No. 28 of 2014 in a normativity context, where the integration points of Islamic law and Indonesian law can be established.